Pedunculated Cecal Lipoma Causing Colo-Colonic Intussusception: A Rare Case Report - Stefanos Atmatzidis; Grigoris Chatzimavroudis; Aristidis Patsas; Basilis Papaziogas; Spiros Kapoulas; Stelios Kalaitzis; Ananias Ananiadis; John Makris; Konstantinos Atmatzidis (Case Reports in Surgery)
Colonic lipomas are uncommon nonepithelial neoplasms that are typically sessile, asymptomatic and incidentally found during endoscopy, surgery, or autopsy. We present a very rare case of a 34-year-old female patient with symptomatic pedunculated cecal lipoma causing intermittent colo-colonic intussusception. Despite adequate imaging studies, definite preoperative diagnosis was not established and the patient underwent exploratory laparotomy. Intraoperatively, intussusception of the cecum into the ascending colon was found and right hemicolectomy was performed. Macroscopic assessment of the resected specimen showed the presence of a giant cecal pedunculated polypoid tumor with features of lipoma, causing intussusception. Histopathological examination confirmed the diagnosis of pedunculated cecal lipoma.